Keynes on Monetary Policy, Finance and Uncertainty : Reassessing Liquidity Preference Theory. - Bibow, Jrg (Taylor & Francis, 2000)
In this book, Jrg Bibow illustrates how Keynes' methodology inspired his economic theorizing and how this led to fundamental insights concerning the role of money that contrasted with orthodox closed-system modelling.